The Challenge of African Art Music - Agawu, Kofi (Circuit)

(untitled) (Les Presses de l’Université de Montréal, 2011)
This essay offers broad reflection on some of the challenges faced by African composers of art music. The specific point of departure is the publication of a new anthology, Piano Music of Africa and the African Diaspora, edited by Ghanaian pianist and scholar William Chapman Nyaho and published in 2009 by Oxford University Press. The anthology exemplifies a diverse range of creative achievement in a genre that is less often associated with Africa than urban ‘popular’ music or ‘traditional’ music of pre-colonial origins. Noting the virtues of musical knowledge gained through individual composition rather than ethnography, the article first comments on the significance of the encounters of Steve Reich and György Ligeti with various African repertories. Then, turning directly to selected pieces from the anthology, attention is given to the multiple heritage of the African composer and how this affects his or her choices of pitch, rhythm and phrase structure. Excerpts from works by Nketia, Uzoigwe, Euba, Labi and Osman serve as illustration.